Laminated structure, cable and tube
Patent Information
- Application Number
- JP2021098350
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-11
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-06-11
AI Technical Summary
【0011】 本発明によれば、シリコーンゴムを母材とする積層構造体であって、UV-C光への耐性に優れる積層構造体、並びにその積層構造体からなる絶縁体を備えたケーブル及びチューブを提供することができる。
Smart Images

Figure 0007635645000005 
Figure 0007635645000006 
Figure 0007635645000007
Abstract
Description
[Technical Field]
[0001] The present invention relates to laminate structures, cables and tubes. [Background technology]
[0002] Conventionally, medical device cables have been known that are made of silicone rubber containing fine particles and have a coating that covers the sheath (see Patent Document 1). Compared to polyvinyl chloride (PVC), which has traditionally been used as a sheath material, silicone rubber has advantages such as almost no discoloration over time, but its surface tends to have low slipperiness.
[0003] The coating of the cable described in Patent Document 1 is made of silicone rubber containing fine particles, and therefore the surface has irregularities resulting from the fine particles. These irregularities can reduce the contact area when the coating comes into contact with other components, thereby improving the slipperiness of the coating surface, and therefore the slipperiness of the cable. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6723489 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, sterilization by UV-C light irradiation has been attracting attention as a simple, inexpensive, and reliable method for sterilizing medical device cables, but the cable's resistance to UV-C light is an issue when sterilizing by UV-C light irradiation.It has also been confirmed that cables with silicone rubber sheaths deteriorate when repeatedly irradiated with UV-C light, and that cracks can appear in the sheath when the cable is subjected to stress, such as bending.
[0006] The object of the present invention is to provide a laminated structure having a silicone rubber base material and having excellent resistance to UV-C light, as well as a cable and a tube having an insulator made of the laminated structure. [Means for solving the problem]
[0007] The present invention aims to solve the above problems, The base material is silicone rubber, and the first TiO 2 A first layer containing fine particles and a second TiO 2 a second layer containing fine particles, wherein the Ti concentration of the first layer is 0.35 mass% or more and 3.0 mass% or less, the Ti concentration of the second layer is 1.0 mass% or more and 4.4 mass% or less, and the Ti concentration of the second layer is higher than the Ti concentration of the first layer; 1404J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light of 1404 J / cm is 250% or more, and 2 The present invention provides a laminated structure in which, when a bending test equivalent to 45 to 50% tensile strength is conducted after irradiation with UV-C ultraviolet light, cracks are observed in three or fewer areas of 1.5 mm × 4.5 mm at ten locations on the surface at a magnification of 50 times using an optical microscope.
[0008] Furthermore, the present invention aims to solve the above problems, The base material is silicone rubber, and the first TiO 2 A first layer containing fine particles and a second TiO 2 a second layer containing fine particles, wherein the Ti concentration of the first layer is 0.35 mass% or more and 3.0 mass% or less, the Ti concentration of the second layer is 1.0 mass% or more and 4.4 mass% or less, and the Ti concentration of the second layer is higher than the Ti concentration of the first layer; 2808J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light of 2808 J / cm is 150% or more, and 2 The present invention provides a laminated structure in which, when a bending test equivalent to 45 to 50% tensile strength is conducted after irradiation with UV-C ultraviolet light, cracks are observed in three or fewer areas of 1.5 mm × 4.5 mm at ten locations on the surface at a magnification of 50 times using an optical microscope.
[0009] Furthermore, in order to solve the above-mentioned problems, the present invention provides a laminated structure comprising: a first layer having a silicone rubber base material and containing first TiO2 microparticles; and a second layer having a silicone rubber base material and containing second TiO2 microparticles laminated on the first layer, wherein the Ti concentration of the first layer is 0.35 mass% or more and 3.0 mass% or less, and the Ti concentration of the second layer is 1.0 mass% or more and 4.4 mass% or less.
[0010] Furthermore, in order to solve the above problems, the present invention provides a cable or a tube having an insulator made of the above laminated structure. [Effects of the Invention]
[0011] According to the present invention, it is possible to provide a laminated structure having a silicone rubber base material and having excellent resistance to UV-C light, as well as a cable and a tube having an insulator made of the laminated structure. [Brief explanation of the drawings]
[0012] [Figure 1] FIG. 1 is a vertical cross-sectional view of a laminated structure according to a first embodiment of the present invention. [Figure 2] FIG. 2 is a graph showing preferred ranges of the Ti concentration in the first layer and the Ti concentration in the second layer. [Figure 3] FIG. 3 is a plan view schematically showing the configuration of an ultrasonic probe cable according to a second embodiment of the present invention. [Figure 4] 4(a) is a cross-sectional view in the radial direction of the ultrasonic probe cable, and FIG. 4(b) is a cross-sectional view in the radial direction of the ultrasonic probe cable cut along the cutting line AA shown in FIG. [Figure 5] 5(a) to 5(c) are cross-sectional views in the radial direction of a medical tube according to a second embodiment of the present invention. [Figure 6] Figure 6(a) is a graph showing the results of the tensile test on sample B1, and Figure 6(b) is a graph showing the results of the tensile test on sample B2. [Figure 7] Figure 7(a) is a graph showing the results of the tensile test of sample B3, and Figure 7(b) is a graph showing the results of the tensile test of sample B4. [Figure 8] Fig. 8(a) is a graph showing the relationship between UV-C light irradiation time and stress at break of the substrate for samples B1 to B4, and Fig. 8(b) is a graph showing the relationship between UV-C light irradiation time and elongation at break of the substrate for samples B1 to B4. [Figure 9]Fig. 9(a) is a schematic diagram showing the state of the bending test, and Fig. 9(b) is a cross-sectional view of the conductor wire and the sheath piece wound around the conductor wire in the radial direction of the conductor wire. [Figure 10] Figures 10(a) and (b) are SEM observation images of the surface and cross section of a sheath piece cut out from sample C6 irradiated with UV-C light at an irradiation energy of 2808 J / cm2. [Figure 11] Figures 11(a) and (b) are SEM images of the surface and cross section of a sheath piece cut out from sample C7 irradiated with UV-C light at an irradiation energy of 2808 J / cm2. [Figure 12] FIG. 12 shows typical observation images of the surfaces of sheath pieces cut out from samples C1 to C11 after bending tests. [Figure 13] 13(a), (b), (c), and (d) are graphs showing the relationship between the irradiation energy of UV-C light and the elongation at break for samples D1, D3, D4, and D7, respectively. [Figure 14] 14(a), (b), (c), and (d) are graphs showing the relationship between the irradiation energy of UV-C light and the elongation at break for samples D8, D9, D10, and D11, respectively. [Figure 15] 15(a) and (b) are graphs plotting the relationship between the Ti concentration in the first layer and the elongation at break. [Figure 16] Figures 16(a) and (b) are observation images of the surfaces of sample C11 and sample C12, respectively, before the wiping test. [Figure 17] Figures 17(a) and (b) are observation images of the surfaces of specimens C11 and C12, respectively, after the wiping test. DETAILED DESCRIPTION OF THE INVENTION
[0013] [First embodiment] (Configuration of laminated structure) 1 is a vertical cross-sectional view of a laminated structure 1 according to a first embodiment of the present invention. The laminated structure 1 includes a first layer 10 having a silicone rubber base material 101 and containing titanium oxide (TiO2) particles 102, and a second layer 11 laminated on the first layer 10, having a silicone rubber base material 111 and containing titanium oxide (TiO2) particles 113.
[0014] Silicone rubber, which is the base material of the first layer 10 and the second layer 11, is a type of silicone resin. Silicone rubber has higher resistance to ultraviolet rays (UV-A light and UV-B light) than polyvinyl chloride, which has traditionally been used as a material for cables and tubes used in medical applications.
[0015] The laminated structure 1 can take various forms depending on its application. For example, it is molded into a tubular shape when used as an insulator for cables or tubes, and it is molded into a sheet when used as a highly UV-resistant sheet for a constant temperature greenhouse or an UV-shielding sheet (UV-shielding curtain) for blocking UV rays leaking from a sterilization chamber or the like.
[0016] (Second layer configuration) For example, an addition reaction type silicone rubber coating agent or a condensation reaction type silicone rubber coating agent can be used as the silicone rubber that is the base material 111 of the second layer 11. In particular, it is preferable to use an addition reaction type silicone rubber coating agent from the viewpoints of adhesion to the first layer 10, which has silicone rubber as its base material, and abrasion resistance.
[0017] In order to obtain good slipperiness and a predetermined wiping resistance on the surface of the laminated structure 1 by the second layer 11, the thickness of the second layer 11 is preferably 3 μm or more. The second layer 11 may be laminated on both sides of the first layer 10. There is no particular upper limit to the thickness of the second layer 11, but from the viewpoints of productivity, high flexibility, and high bendability, it is preferably 100 μm or less.
[0018] The TiO2 particles 113 contained in the second layer 11 can block UV-C light by absorbing and / or scattering it. Here, UV-C light is ultraviolet light in the wavelength range of 200 to 280 nm. By blocking UV-C light with the TiO2 particles 113, deterioration of the silicone rubber base material 111 due to UV-C light can be suppressed. The TiO2 constituting the TiO2 particles 113 may be any of anatase type, rutile type, or brookite type, or may be a mixture of two or more types. Furthermore, niobium oxide may be added to titanium oxide to provide stability.
[0019] 1, second layer 11 preferably contains fine particles 112 for imparting irregularities to the surface of second layer 11. When the surface is irregular, the contact area between second layer 11 and an object is smaller than when the surface is flat, and the slipperiness is increased.
[0020] The microparticles 112 include, for example, at least one of silicone resin microparticles, silicone rubber microparticles, and silica microparticles. Silicone resin, which has fewer reactive groups (e.g., methyl groups) than silicone rubber, has a higher hardness than silicone rubber, and silica, which has no reactive groups, has an even higher hardness. In terms of density, silica has the highest density, followed by silicone resin and silicone rubber, with the lowest.
[0021] In order to suppress deformation of the surface irregularities of the second layer 11 when it comes into contact with a contacting object, it is preferable that the microparticles 112 have a high hardness. This is because, when a pressing pressure is applied to the surface of the second layer 11 by the contacting object, the higher the hardness of the microparticles 112, the more the deformation of the surface irregularities of the second layer 11 can be suppressed. This suppresses an increase in the contact area of the second layer 11 with the contacting object, and makes it possible to maintain slipperiness. Therefore, from the viewpoint of suppressing deformation of the surface irregularities of the second layer 11 when it comes into contact with the contacting object, silica microparticles are most preferable as the microparticles 112, and silicone resin microparticles are next most preferable.
[0022] On the other hand, because silica has a high density as described above, silica microparticles tend to settle in the silicone rubber coating agent, which is the base material during the manufacturing process of second layer 11, and are more difficult to disperse in the silicone rubber coating agent (in second layer 11) than silicone resin microparticles or silicone rubber microparticles. Therefore, from the viewpoint of improving the uniformity of dispersion in the silicone rubber coating agent (in second layer 11), silicone rubber microparticles are most preferable as microparticles 112, and silicone resin microparticles are next most preferable.
[0023] Therefore, in order to maintain the slipperiness of the second layer 11 when it comes into contact with a contact object and to ensure uniform dispersion of the microparticles 112 in the base material 111 made of silicone rubber, it is preferable to use silicone resin microparticles as the microparticles 112.
[0024] Additionally, the bond energy between atoms in the molecular structure of silicone resin and silica is higher than the bond energy between atoms in the molecular structure of silicone rubber, making silicone resin and silica more resistant to UV-C light than silicone rubber.
[0025] For example, the C-H bonds present in large quantities in silicone rubber have a bond energy (approximately 4.27 eV) smaller than the energy of UV-C light (approximately 6.2 eV), and therefore are broken by irradiation with UV-C light, whereas the Si-O bonds present in large quantities in silicone resin have a bond energy (approximately 6.52 eV) greater than the energy of UV-C light, and therefore are not broken by irradiation with UV-C light. For this reason, from the viewpoint of resistance to UV-C light, it is preferable to use silicone resin microparticles or silica microparticles as the microparticles 112.
[0026] The average particle size of the particles 112 is, for example, 1 μm or more and 10 μm or less. The concentration (mass %) of the particles 112 in the second layer 11 is, for example, 10 mass % or more and 60 mass % or less. Here, the "average particle size" in this specification refers to a particle size measured by a laser diffraction scattering method.
[0027] (First layer configuration) The first layer 10 contains TiO2 particles 102 for blocking UV-C light by absorbing and / or scattering, similar to the second layer 11 which contains TiO2 particles 113 to suppress degradation due to UV-C light that has passed through the second layer 11.
[0028] As described above, the base material 101 is made of silicone rubber, but when the first layer 10 is used as a sheath material, silicone rubber to which general compounding agents such as various cross-linking agents, cross-linking catalysts, antioxidants, plasticizers, lubricants, fillers, flame retardants, stabilizers, colorants, etc. have been added may also be used as the base material 101.
[0029] (TiO2 fine particles) FIG. 2 is a graph showing preferred ranges of the Ti concentration in the first layer 10 containing TiO 2 particles 102 and the Ti concentration in the second layer 11 containing TiO 2 particles 113.
[0030] 2, the Ti concentration in the first layer 10 is preferably 0.35% by mass or more and 3.0% by mass or less. When the first layer 10 contains TiO2 particles 102 at a concentration such that the Ti concentration is 0.35% by mass or more, a high elongation at break can be maintained when a cable including the laminated structure 1 as an insulator (sheath and its coating) is irradiated with UV-C light and then subjected to a tensile test specified in "JIS K6251 (1994)." A specific method for this tensile test will be described later.
[0031] On the other hand, if the first layer 10 contains TiO2 particles 102 with a Ti concentration exceeding 3.0% by mass, the first layer 10 becomes hard, reducing the flexibility and tear strength of the laminated structure 1. Therefore, when the first layer 10 is used as an insulator for a cable or tube, and considering the handleability of the cable or tube, it is preferable that the Ti concentration in the first layer 10 be 3.0% by mass or less.
[0032] 2, the Ti concentration in the second layer 11 is preferably 1.0 mass % or more and 4.4 mass % or less. When the second layer 11 contains TiO2 particles 113 at a concentration such that the Ti concentration is 1.0 mass % or more, the fluence of 1404 J / cm 2 In a bending test equivalent to 45 to 50% tensile strength after irradiation with UV-C light, the occurrence of cracks on the surface of the laminated structure 1 that reach the first layer 10 can be suppressed. The method of the bending test and the method of observing whether or not cracks are present will be described later.
[0033] On the other hand, if the second layer 11 contains TiO2 particles at a concentration exceeding 4.4% by mass, the surface roughness of the second layer 11 increases. As the surface roughness increases, dirt and bacteria become more likely to adhere and become more difficult to remove. Furthermore, if the second layer 11 contains particles 112 such as silicone resin particles, containing TiO2 particles at a concentration exceeding 4.4% by mass reduces the adhesion between the silicone rubber base material 111 and the particles 112, making the particles 112 more likely to fall off and reducing the surface slipperiness of the second layer 11. Therefore, the Ti concentration in the second layer 11 is preferably 4.4% by mass or less.
[0034] 2, it is preferable that the concentration of TiO2 particles 113 contained in the second layer 11 is higher than the concentration of TiO2 particles 102 contained in the first layer 10, i.e., the Ti concentration in the second layer 11 is higher than the Ti concentration in the first layer 10. By making the concentration of TiO2 particles 113 in the second layer 11 higher than the concentration of TiO2 particles 102 in the first layer 10, UV-C light can be effectively absorbed and / or scattered in the second layer 11, deterioration of the first layer 10 due to UV-C light can be suppressed, and a decrease in the flexibility and tear strength of the laminated structure 1 can be suppressed.
[0035] All Ti in the first layer 10 is contained in TiO2 particles 102, and all Ti in the second layer 11 is contained in TiO2 particles 113. The Ti concentrations in the first layer 10 and the second layer 11 are determined as average values in a measurement area of 125 μm wide × 95 μm long using an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (SEM).
[0036] Second Embodiment The second embodiment of the present invention is a cable or tube provided with an insulator made of the laminated structure 1 according to the first embodiment. As an example, a cable used as an ultrasonic probe cable for medical use will be described below.
[0037] Fig. 3 is a plan view schematically showing the configuration of an ultrasonic probe cable 2 according to a second embodiment of the present invention. In the ultrasonic probe cable 2, as shown in Fig. 3, an ultrasonic probe 32 is attached to one end of a cable 20 via a boot 31 that protects the one end. Meanwhile, a connector 33 that is connected to the main body of an ultrasonic imaging device is attached to the other end of the cable 20.
[0038] 4(a) is a radial cross-sectional view of the cable 20 of the ultrasound probe cable 2. Electric wires 21, typically a plurality of coaxial cables, are housed inside the cable 20, and a shield 22, such as a braided shield, is provided to cover the plurality of electric wires 21. A sheath 23 is provided to cover the shield 22. Furthermore, the cable 20 is formed with a coating 24 that covers the periphery of the sheath 23 and is in close contact with the sheath 23.
[0039] 4(b) is a radial cross-sectional view of the ultrasonic probe cable 2 taken along the cutting line AA in FIG. 3. As shown in FIG. 4(b), the boot 31 is attached to the coating 24 via an adhesive layer 34 so as to cover the coating 24. The adhesive layer 34 is formed of, for example, a silicone adhesive or an epoxy adhesive. The boot 31 may also be formed of, for example, PVC, silicone rubber, chloroprene rubber, or the like, and preferably contains TiO2 microparticles 102 or an organic ultraviolet absorber for blocking UV-C light, similar to the first layer 10.
[0040] The sheath 23 and coating 24 of the cable 20 are respectively composed of the first layer 10 and the second layer 11 of the laminated structure 1. That is, in the cable 20, the laminated structure 1 is used as the sheath 23 and the coating 24. Note that the TiO2 particles 102 in the sheath 23 and the particles 112 and TiO2 particles 113 in the coating 24 are not shown in the figure.
[0041] The cable 20 has excellent resistance to UV-C light because the laminated structure 1, which has excellent resistance to UV-C light, is used as the insulator (sheath 23 and coating 24) of the cable 20. Furthermore, when the second layer 11 of the laminated structure 1 contains fine particles 112, the cable 20 has excellent surface slipperiness, and can prevent snagging caused by the stickiness of the surface of the sheath 23. The thickness of the coating 24 is, for example, 3 μm or more and 100 μm or less.
[0042] Furthermore, when the first layer 10 contains TiO2 particles 102 with a Ti concentration of 0.35 mass % or more and 3.0 mass % or less, and the second layer 11 contains TiO2 particles 113 with a Ti concentration of 1.0 mass % or more and 4.4 mass % or less, the insulator (sheath 23 and coating 24) of the cable 20 has a thermal conductivity of 1404 J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light is 250% or more, and the elongation at break is 1404 J / cm 2In the laminated structure 1 having the second layer 11 not containing the TiO2 microparticles 102, the elongation at break before irradiation with UV-C light is 250% or more (see FIG. 7(b)). Therefore, the elongation at break before irradiation with UV-C light is 1404 J / cm 2 The goal was to achieve an elongation at break of 250% or more even after irradiation with UV-C light.
[0043] Furthermore, when the first layer 10 contains TiO2 particles 102 with a Ti concentration of 0.35 mass % or more and 3.0 mass % or less, and the second layer 11 contains TiO2 particles 113 with a Ti concentration of 1.0 mass % or more and 4.4 mass % or less, the insulator (sheath 23 and coating 24) of the cable 20 has a thermal conductivity of 2808 J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light is 150% or more, and the elongation at break is 2808 J / cm 2 The occurrence of cracks on the surface of the second layer 11 can be suppressed in a bending test equivalent to 45 to 50% tension after irradiation with UV-C light. Since the elongation at break required for a general rubber material is 150% or more, the elongation at break of 2808 J / cm 2 The target was set separately for the elongation at break to be 150% or more even after irradiation with UV-C light.
[0044] If the concentration of TiO2 particles contained in the first layer 10 is high, there is a risk of a decrease in the flexibility and tear strength of the first layer 10. Therefore, it is preferable to increase the concentration of TiO2 particles contained in the second layer 11 to block UV-C light in the second layer 11. When the concentration of TiO2 particles 113 contained in the second layer 11 is higher than the concentration of TiO2 particles 102 contained in the first layer 10, deterioration of the first layer 10 due to UV-C light can be suppressed, and a decrease in the flexibility and tear strength of the insulator (sheath 23 and coating 24) of the cable 20 can be suppressed.
[0045] Next, an example of a method for manufacturing the ultrasonic probe cable 2 according to this embodiment will be described. First, a plurality of electric wires 21 (for example, 100 or more) are bundled together. Then, a shield 22 is formed so as to cover the bundled electric wires 21.
[0046] Next, the first layer 10 and the second layer 11 of the laminated structure 1 are formed in this order to cover the shield 22, thereby forming the sheath 23 and the coating 24. The sheath 23 is formed, for example, by extrusion molding using an extruder. The coating 24 is formed, for example, by a dipping method, a spray coating method, a roll coating method, or the like. In the dipping method, the ultrasonic probe cable 2 formed up to the sheath 23 is pulled up through a liquid coating material, thereby forming the coating 24 on the surface of the sheath 23. This dipping method is superior to the spray coating method and the roll coating method in terms of the uniformity of the thickness of the coating 24 formed.
[0047] The liquid coating agent used in the dipping method is a liquid silicone rubber containing fine particles 112 and TiO2 fine particles 113, and also contains an organic solvent. The content of the fine particles 112 and TiO2 fine particles 113 in the coating 24 can be controlled by adjusting the content of the fine particles 112 and TiO2 fine particles 113 in this liquid coating agent. Examples of organic solvents that can be used include aromatic hydrocarbon solvents such as toluene and xylene, and aliphatic hydrocarbon solvents such as n-hexane, n-heptane, n-octane, isooctane, nonane, decane, undecane, and dodecane, either alone or in combination. Other examples include alcohols such as ethanol and isopropyl alcohol, and acetone.
[0048] Further, as another example of a cable or tube having an insulator made of the laminated structure 1, the structure of a tube (hollow pipe) used for medical purposes such as a catheter will be described below.
[0049] Figures 5(a) to 5(c) are radial cross-sectional views of medical tubing according to a second embodiment of the present invention. Medical tubing 40a shown in Figure 5(a) has an outer coating 42 on the outer surface 41a of a tubing body 41. Medical tubing 40b shown in Figure 5(b) has an inner coating 43 on the inner surface 41b of the tubing body 41. Medical tubing 40c shown in Figure 5(c) has an outer coating 42 and an inner coating 43 on the outer surface 41a and inner surface 41b of the tubing body 41, respectively.
[0050] As exemplified by medical tubes 40a, 40b, and 40c, the tube according to this embodiment comprises a tube body 41, an outer coating 42 covering the outer surface 41a of the tube body 41, an inner coating 43 covering the inner surface 41b of the tube body 41, or both the outer coating 42 and the inner coating 43.
[0051] The tube body 41 of the medical tubes 40a, 40b, and 40c is made of the first layer 10 of the laminated structure 1, and the outer coating 42 and the inner coating 43 are made of the second layer 11 of the laminated structure 1. Therefore, the medical tubes 40a, 40b, and 40c have excellent resistance to UV-C light, similar to the cable 20 of the ultrasound probe cable 2 described above.
[0052] Furthermore, when the second layer 11 of the laminated structure 1 contains the microparticles 112, the inner and outer surfaces have excellent slip properties, which allows for smooth insertion and removal of instruments when inserted into a tube, such as a medical tube such as a catheter. Additionally, the tube according to this embodiment can be used for endoscopic surgical instrument tube sets, ultrasonic surgical instrument tube sets, blood analyzer tubes, piping within oxygen concentrators, artificial dialysis blood circuits, cardiopulmonary bypass circuits, endotracheal tubes, etc.
[0053] (Effects of the embodiment) According to the first embodiment, it is possible to provide the laminated structure 1 having excellent resistance to UV-C light. Also, according to the second embodiment, it is possible to provide the ultrasound probe cable 2 and medical tubes 40a, 40b, and 40c having excellent resistance to UV-C light by using the laminated structure 1 as an insulator. [Example]
[0054] (Fabrication of laminated structure 1) Four types of samples (referred to as samples A1 to A4) were prepared to verify the UV-C light blocking effect of the second layer 11 of the laminated structure 1. First, 200 coaxial cables with a diameter of approximately 0.25 mm were twisted together and covered with a braided wire to prepare a cable core. Next, using an extruder, a sheath material was extruded around the cable core at a speed of 5 m / min to form a 0.8 mm-thick sheath 23 as the first layer 10 of the laminated structure 1 (cable outer diameter: approximately 8 mm). The sheath material of sample A1 was commonly used PVC. The sheath material of samples A2 to A4 was a color batch containing titanium oxide (a mixture of "KE-color-W" and "KE-174-U" manufactured by Shin-Etsu Chemical Co., Ltd.). The Ti concentration was analyzed by an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (SEM) (average value in a measurement area of 125 μm wide × 95 μm long) to be 0.12 mass %. Through the steps up to this point, samples A1 and A2 not having the coating 24 as the second layer 11 of the laminate structure 1 were produced.
[0055] Next, materials for forming the coating 24 of sample A3 were prepared. An addition reaction type silicone rubber coating agent (product name: SILMARK-™, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as the rubber component for the base material 111. Silicone resin microparticles (product name: X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd.) with an average particle size of 5 μm were also prepared as the microparticles 112. 100 parts by mass of this rubber component were mixed with 120 parts by mass of the silicone resin microparticles, 600 parts by mass of toluene as a viscosity adjusting solvent, 8 parts by mass of a crosslinking agent (product name: CAT-™, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.3 parts by mass of a curing catalyst (product name: CAT-PL-2, manufactured by Shin-Etsu Chemical Co., Ltd.) to prepare a coating solution in which the ratio of the microparticles 112 to the coating 24 was 55% by mass. The content of the microparticles 112 in the coating 24 was calculated assuming that the coating agent hardens with almost no mass loss (approximately equivalent to the blending mass ratio).
[0056] Next, the surface of the sheath 23 provided on the cable core was cleaned. After that, the cable core provided with the sheath 23 was immersed in the coating solution by dip coating to form a coating film made of silicone rubber on the surface of the sheath. The coating film was then subjected to a thorough drying and curing treatment at a temperature of 150°C to form a coating film 24 having an uneven surface. The thickness of the coating film 24 of the obtained sample A3 was 15 μm. Sample A3 was produced by the above steps.
[0057] Next, materials for forming the coating 24 of sample A4 were prepared. For the coating 24 of sample A4, in addition to the same rubber component as used for the coating 24 of sample A3, which served as the base material 111, and silicone resin microparticles as the microparticles 112, anatase-type TiO microparticles with an average particle size of 250 nm were prepared as the TiO microparticles 113. Then, 120 parts by mass of the silicone resin microparticles, the TiO microparticles, 600 parts by mass of toluene as a viscosity adjusting solvent, 8 parts by mass of a crosslinking agent (product name: CAT-TM, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.3 parts by mass of a curing catalyst (product name: CAT-PL-2, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed with 100 parts by mass of the rubber component to prepare a coating solution in which the ratio of the microparticles 112 to the coating 24 was 55% by mass, and the ratio of the TiO microparticles 113 to the coating 24 was a predetermined concentration. The concentration of the TiO2 particles 113 was adjusted so that the titanium concentration in the coating 24 (average value in a measurement area of 125 μm wide × 95 μm long) was 0.6 mass % as determined by an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (SEM). The content of the particles 112 in the coating 24 was calculated on the assumption that the coating agent hardens with almost no mass loss (almost equivalent to the blending mass ratio).
[0058] Next, in the same manner as for the coating 24 of sample A3, the surface of the sheath 23 was cleaned, a coating film was formed by dip coating, and the coating film was dried and cured to form a coating 24 having an uneven surface. The thickness of the obtained coating 24 of sample A4 was 15 μm. Sample A4 was produced by the above steps.
[0059] (Verification of resistance to UV-C light) To verify the resistance of the laminated structure 1 to UV-C light, tensile tests were performed on samples A1 to A4 before and after UV-C light irradiation. First, a slit was made along the length of the sheath 23 of each cable-shaped sample A1 to A4 (the sheath 23 was covered with the coating 24 in samples A3 and A4) prepared by the above method, and the contents inside the sheath 23 were removed and the sheath 23 was opened. The opened sheath 23 was then punched out with a No. 6 dumbbell to prepare a dumbbell test specimen (0.8 mm thick). Here, the dumbbell test specimens formed from the sheaths 23 of samples A1, A2, A3, and A4 (the sheaths 23 covered with the coating 24 in samples A3 and A4) are designated samples B1, B2, B3, and B4, respectively. Table 1 below shows the configurations of samples B1 to B4.
[0060] [Table 1]
[0061] The tensile test was performed on the above samples B1 to B4 in accordance with JIS K6251 (1994) at an ambient temperature of 15 to 35°C, an ambient humidity of 28 to 65% RH, and atmospheric pressure. UV-C light irradiation was performed using a storage cabinet with a germicidal lamp (Daishin Kogyo Co., Ltd. DM-5, Lamp GL-10) at an internal temperature of 25 to 40°C, an internal humidity of 28 to 65%, an internal pressure of 1 atmosphere (atmospheric pressure), a wavelength of 253.7 nm, and an illuminance of 1.3 mW / cm. 2 The experiment was carried out under the condition of irradiation times of 100 and 200 hours. The illuminance meter used was the UVC-254A manufactured by MK Scientific.
[0062] Figure 6(a) is a graph showing the results of a tensile test on sample B1. In Figure 6(a), "Unirradiated" indicates sample B1 before UV-C light irradiation, while "After irradiation" indicates sample B1 after 200 hours of UV-C light irradiation. As shown in Figure 6(a), the strength (the amount of stress at which the substrate breaks) and elongation were lower after UV-C light irradiation than before irradiation, confirming that sample B1 deteriorated (changed to make it more susceptible to breakage) due to UV-C light irradiation. Furthermore, since sample B1 was made of gray PVC, a yellowish discoloration was visually confirmed upon UV-C light irradiation. Note that 100% elongation indicates that the length of the dumbbell test specimen had doubled from its original length.
[0063] Figure 6(b) is a graph showing the results of the tensile test for sample B2. In Figure 6(b), "Unirradiated" indicates sample B2 before UV-C light irradiation, while "After irradiation" indicates sample B2 after 200 hours of UV-C light irradiation. As shown in Figure 6(b), the strength and elongation were lower after UV-C light irradiation than before, confirming that sample B2 deteriorated (degraded) due to UV-C light irradiation. Furthermore, no discoloration due to UV-C light irradiation was visually observed for sample B2 (white), which was made of silicone rubber. However, a comparison with the graph in Figure 6(a) reveals that silicone rubber deteriorated more than PVC due to UV-C light irradiation.
[0064] Although sample B2 contains TiO2 particles that absorb UV-C light, the concentration is low (Ti concentration in sheath 23 is 0.12 mass%), so it is thought that this had almost no effect on the resistance to UV-C light. Also, sample B2 does not have a coating corresponding to second layer 11, so its surface slipperiness is inferior to samples B3 and B4.
[0065] Figure 7(a) is a graph showing the results of a tensile test on sample B3. In Figure 7(a), "Unirradiated" indicates sample B3 before UV-C light irradiation, while "After irradiation" indicates sample B3 after 200 hours of UV-C light irradiation. As shown in Figure 7(a), the strength and elongation were lower after UV-C light irradiation than before irradiation, confirming that sample B3 deteriorates due to UV-C light irradiation. Furthermore, similar to sample B2, sample B3 (white) did not show any visible discoloration due to UV-C light irradiation.
[0066] 7(a), cracks occurred in the coating 24 corresponding to the second layer 11 when the elongation exceeded 50%. The coating 24 of sample B3 contains silicone resin microparticles as the microparticles 112, which have excellent resistance to UV-C light, and it is believed that the silicone rubber in the areas where these silicone resin microparticles are not present deteriorated, causing the cracks.
[0067] Figure 7(b) is a graph showing the results of a tensile test on sample B4. In Figure 7(b), "Unirradiated" indicates sample B4 before UV-C light irradiation, while "After irradiation" indicates sample B4 after 200 hours of UV-C light irradiation. As shown in Figure 7(b), the strength and elongation were nearly equal before and after UV-C light irradiation, confirming that degradation of sample B4 due to UV-C light irradiation was effectively suppressed. Furthermore, like sample B2, sample B4 (white) did not show any visible discoloration due to UV-C light irradiation.
[0068] Comparing the test results of sample B4 with those of sample B3, it can be seen that the TiO2 fine particles contained in the coating corresponding to the second layer 11 blocked UV-C light, thereby suppressing deterioration.
[0069] Fig. 8(a) is a graph showing the relationship between UV-C light irradiation time and the stress at break of the substrate for samples B1 to B4, and Fig. 8(b) is a graph showing the relationship between UV-C light irradiation time and the elongation at break of the substrate for samples B1 to B4.
[0070] 8(a) and (b), sample B3, which does not contain TiO2 microparticles in the coating corresponding to the second layer 11, shows a decrease in strength and elongation as the UV-C light irradiation time increases. On the other hand, sample B4, which contains TiO2 microparticles in the coating corresponding to the second layer 11, shows no change in strength or elongation even with an increase in UV-C light irradiation time. Furthermore, while sample B4's elongation before UV-C light irradiation is inferior to that of sample B1, its elongation after 200 hours of UV-C light irradiation is superior to that of sample B1. These results also show that the TiO2 microparticles contained in the coating of sample B4 can suppress the progression of degradation caused by UV-C light. [Example]
[0071] (Fabrication of laminated structure 1) Eleven types of samples (referred to as samples C1 to C11) were fabricated to verify the resistance of the laminated structure 1 to UV-C light. Each of samples C1 to C11 includes a first layer 10 and a second layer 11, with TiO particles 102 contained in the first layer 10. Of samples C1 to C11, samples C1, C6, and C9 do not include TiO particles 113 in the second layer 11 and were fabricated using the same process and materials as sample A3 in Example 1. Furthermore, samples C2 to C5, C7, C8, C10, and C11 include TiO particles 113 in the second layer 11 (Ti concentration of 1.5 mass % or 1.9 mass %) and were fabricated using the same process and materials as sample A4 in Example 1. Table 2 below shows the configurations of the sheath 23 and coating 24 of samples C1 to C11. The thickness of the first layer 10 (sheath 23) was 0.8 mm, and the thickness of the second layer 11 (coating 24) was 20 μm.
[0072] [Table 2]
[0073] (UV-C light resistance verification) To verify the resistance of laminate structure 1 to UV-C light from the bending strength, a bending test equivalent to 45-50% tensile strength was carried out on samples C1 to C11 after UV-C light irradiation. UV-C light irradiation was carried out using a storage cabinet with a germicidal lamp (Daishin Kogyo Co., Ltd. DM-5, Lamp GL-10) at an internal temperature of 25-40°C, internal humidity of 28-65%, internal pressure of 1 atmosphere (atmospheric pressure), wavelength of 253.7 nm, and illuminance of 1.3 mW / cm. 2 The tests were conducted for irradiation times of 200, 300, 400, and 600 hours. The illuminance meter used was an MK Scientific UVC-254A. The bending tests were conducted on the above samples C1 to C11 at an ambient temperature of 15 to 35°C, an ambient humidity of 28 to 65% RH, and atmospheric pressure.
[0074] FIG. 9(a) is a schematic diagram showing the state of the bending test. The sheath piece 50 is a portion of the sheath 23 covered with the coating 24, cut from each of the samples C1 to C11. In the bending test, a rectangular sheath piece 50 was first cut from each of the samples C1 to C11 and wrapped around a conductor (metal wire) 51 with a radius of 0.5 mm, as shown in FIG. 9(a). The overlapping portions of the sheath piece 50 were then clamped and fixed from both sides (fixing fixtures are not shown). The sheath pieces 50 were cut from 10 equally spaced locations along the cable length from the 1-m-long cable-shaped samples C1 to C11, each measuring 12 mm (circumferential direction of the cable) × 18 mm (longitudinal direction of the cable). The sheath pieces 50 were then wrapped around the conductor 51 so that the longitudinal side of the cable was aligned with the circumferential direction of the conductor 51 and the second layer 11 was positioned on the outer periphery.
[0075] 9(b) is a cross-sectional view of the conductor 51 and the sheath piece 50 wound around the conductor 51, taken in the radial direction of the conductor 51. If the radius of the conductor 51 is r and the thickness of the sheath piece 50 is t, then as shown in FIG. 9(b), the longitudinal length of the neutral plane 50a of the sheath piece 50 within an arbitrary range of angle θ is (r+t / 2)·θ, and the longitudinal length of the outer circumferential surface 50b of the sheath piece 50 is (r+t)·θ. Therefore, the longitudinal elongation of the outer circumferential surface 50b of the sheath piece 50 wound around the conductor 51 is expressed as {(r+t)·θ-(r+t / 2)·θ} / ((r+t / 2)·θ)×100=t / (2r+t)×100, which is approximately 45% since the radius r of the conductor 51 is 0.5 mm and the thickness t of the sheath piece 50 is 0.82 mm.
[0076] A bending test was carried out on the sheath pieces 50 cut out from samples C1 to C11. The surface of the sheath pieces 50 during the bending test (when the second layer 11 was subjected to an elongation equivalent to 45 to 50%) was observed at 50x magnification using an optical microscope (Keyence Digital Microscope VHX-1000). As a result, the sheath pieces 50 of samples C1, C6, and C9, which did not contain TiO2 microparticles in the second layer 11, had a thermal conductivity of 936 J / cm 2 of irradiation energy (illuminance (W / cm 2 The sample irradiated with UV-C light at 1404 J / cm × irradiation time (seconds) had no cracks on the surface, but 2 , 1872J / cm 2 , 2808J / cm 2 The sample irradiated with UV-C light at this irradiation energy had cracks on the surface.
[0077] On the other hand, the sheath pieces 50 cut out from the samples C2 to C5, C7, C8, C10, and C11 containing TiO2 particles in the second layer 11 had a radiation energy of 936 J / cm 2 , 1404J / cm 2 , 1872J / cm 2 , 2808J / cm 2No cracks were observed on the surface of any of the samples irradiated with UV-C light at this irradiation energy. Note that the cracks referred to in this bending test refer to depressions that extend from the second layer 11 (coating 24) to the first layer 10 (sheath 23).
[0078] Figure 10(a) and (b) show the values of 2808 J / cm 2 11(a) and 11(b) are SEM images of the surface and cross section of a sheath piece 50 cut out from sample C6 irradiated with UV-C light at an irradiation energy of 2808 J / cm. 2 10(a) and 10(b) are SEM images of the surface and cross section of a sheath piece 50 cut out from sample C7 irradiated with UV-C light at an irradiation energy of 1000 . In the SEM images of FIGS. 10(a) and 10(b), a crack 52 is observed that reaches from the second layer 11 to the first layer 10. On the other hand, the recess 53 observed in the SEM images of FIGS. 11(a) and 11(b) does not reach the first layer 10 and is therefore not counted as a crack. FIGS. 10(a) and 11(a) are SEM images observed at 100x magnification, and FIGS. 10(b) and 11(b) are SEM images observed at 1000x magnification. The SEM images are of the sheath piece 50 removed from the conductor 51 after the bending test.
[0079] The results of this bending test were used as one of the criteria for determining whether the laminate structure 1 was resistant to UV-C light. Sheath pieces 50 were collected from 10 locations on each sample irradiated with UV-C light. The bending test was performed on each of these 10 sheath pieces 50, and the number of sheath pieces 50 in which cracks were observed was counted when a 1.5 mm × 4.5 mm area was observed at 50x magnification using an optical microscope. When 10 1.5 mm × 4.5 mm areas on the surface of the sample were observed, if cracks were observed in three or fewer of the 10 1.5 mm × 4.5 mm areas, the laminate structure 1 was determined to be resistant to UV-C light.
[0080] Fig. 12 shows a typical observation image of the surface of the sheath piece 50 when a bending test was performed on the sheath piece 50 cut out from the samples C1 to C11. The observation image in Fig. 12 is an image of an area of 1.5 mm x 4.5 mm on the surface of the sheath piece 50 made from the samples C1 to C11, observed at 50x magnification using an optical microscope (Keyence Digital Microscope VHX-1000). According to Fig. 12, the bending test was performed on the sheath piece 50 cut out from the samples C1 to C11. 2 , 1872J / cm 2 , 2808J / cm 2 of irradiation energy (illuminance (W / cm 2 Cracks were observed on the surface of the sheath pieces 50 of samples C1, C6, and C9, which did not contain TiO2 microparticles in the second layer 11, and were irradiated with UV-C light for 100 s.p.m. / min × irradiation time (seconds). For the sheath pieces 50 cut out from samples C2 to C5, C7, C8, C10, and C11, which contained TiO2 microparticles in the second layer 11, cracks were observed on the surface of the sheath pieces 50 of samples C2 to C5, C7, C8, C10, and C11, which contained TiO2 microparticles in the second layer 11, and were irradiated with UV-C light for 100 s.p.m. / min × irradiation time (seconds). 2 , 1404J / cm 2 , 1872J / cm 2 , 2808J / cm 2 No cracks were observed on the surface of any of the samples irradiated with UV-C light at this irradiation energy.
[0081] For example, 2808 J / cm 2 In samples C10 and C11 after irradiation with this energy, a streak-like pattern is observed along the longitudinal direction of the sample. This pattern does not reach the sheath 23, but is a depression that appears only in the coating 24. In other words, the thickness of the coating 24 is greater than the depth of the depression. Such a depression does not serve as the starting point for fracture of the sheath 23, and therefore, as mentioned above, is not counted as a crack. Whether the streak-like pattern is a crack can also be determined by checking whether the pattern reaches the sheath 23 in cross-sectional SEM observation images such as those shown in Figures 10(b) and 11(b).
[0082] From the results shown in FIG. 12, for samples C2 to C5, C7, C8, C10, and C11, cracks were observed in three or fewer of the ten 1.5 mm × 4.5 mm regions (specifically, zero (no cracks)), and these samples were determined to be resistant to UV-C light. Furthermore, for samples C1, C6, and C9, cracks were observed in four or more of the ten 1.5 mm × 4.5 mm regions, and these samples were determined to be not resistant to UV-C light. From the above, it was found that increasing the content of TiO2 microparticles in the second layer 11 is effective in suppressing cracks in the laminate structure 1. Specifically, it was confirmed that cracks in the laminate structure 1 can be suppressed by setting the Ti concentration in the second layer 11 to 1.0 mass% or more.
[0083] Next, to verify the resistance of the laminated structure 1 to UV-C light from the elongation at break, tensile tests were carried out on the samples C1 to C5 and C7 to C11 after UV-C light irradiation. UV-C light irradiation was carried out using a storage cabinet with a germicidal lamp (Daishin Kogyo Co., Ltd. DM-5, Lamp GL-10) at an internal temperature of 25 to 40°C, an internal humidity of 28 to 65%, an internal pressure of 1 atmosphere (atmospheric pressure), a wavelength of 253.7 nm, and an illuminance of 1.3 mW / cm. 2 The irradiation times were 100, 200, 300, 400, and 600 hours.
[0084] After irradiation with UV-C light, dumbbell test specimens D1-D5 and D7-D11 were formed from cable-shaped specimens C1-C5 and C7-C11, respectively, using a method similar to that used to form specimens B1-B4 from specimens A1-A4 in Example 1. Tensile tests on specimens D1-D5 and D7-D11 (No. 6 dumbbell test specimens) were conducted according to JIS K6251 (1994) using the same method and conditions as those used for specimens B1-B4. The ambient temperature and humidity at the tensile test evaluation site were 25±3°C, 50±10%, and atmospheric pressure. The gage length was 20 mm, and the tensile speed was 500 mm / min until fracture.
[0085] Figure 13 (a), (b), (c), and (d) show the UV-C light irradiation energy (illuminance (W / cm)) for samples D1, D3, D4, and D7, respectively. 2 13(a), (b), (c), and (d) are graphs showing the relationship between UV-C light irradiation energy and elongation at break for samples D8, D9, D10, and D11, respectively. Table 3 below shows the numerical values of the plotted points in FIGS. 13(a), (b), (c), and (d) and FIGS. 14(a), (b), (c), and (d), i.e., the elongation at break (%) values for each sample at each UV-C light irradiation energy.
[0086] [Table 3]
[0087] 13(a) to (d), 14(a) to (d), and Table 3, among the elongations at break of samples D1, D3, D4, and D7 to D11, the elongations at break of samples D7 to D11 were higher when the irradiation energy of UV-C light was 1404 J / cm 2 The elongation at break of samples D7 to D11 was 250% or more even when the UV-C light irradiation energy was 1872 J / cm. 2 The elongation at break of samples D7 to D11 was 200% or more even when the UV-C light irradiation energy was 2808 J / cm. 2 It is clear that samples D7 to D11 have high resistance to UV-C light in terms of elongation at break.
[0088] 13(a) to (d), 14(a) to (d), and Table 3, it was found that increasing the content of TiO2 particles in the first layer 10 is effective in increasing the elongation at break of the laminated structure 1. Furthermore, as shown in FIGS. 15(a) and 15(b), the relationship between the Ti concentration (content of TiO2 particles) in the first layer 10 and the elongation at break (results of D3, D7, and D10, and results of D4, D8, and D11) was plotted and polynomial approximation was performed. FIG. 15(a) shows the elongation at break of 1404 J / cm 2 Figure 15(b) shows the results after irradiation with UV-C light of 2808 J / cm 2 The results are after irradiation with UV-C light of 1404J / cm 2 It was found that the Ti concentration in the first layer 10 should be 0.4 mass % or more in order to ensure that the elongation at break is 250% or more even after irradiation with UV-C light of 2808 J / cm. 2 It was found that in order to ensure that the elongation at break is 150% or more even after irradiation with UV-C light, the Ti concentration in the first layer 10 should be 0.35 mass% or more.
[0089] Next, a surface wiping test was conducted on Sample C11, which contained TiO particles 113 in the second layer 11 (coating 24) with a Ti concentration of 1.9 mass %, and a sample (referred to as Sample C12) prepared in the same manner as Sample C11 but containing TiO particles 113 in the second layer 11 with a Ti concentration of 4.4 mass %. The preparation and testing of the sample for this wiping test were conducted using the same method as in Japanese Patent No. 6723489. The preparation and measurement of samples for measuring the static friction coefficient before and after the wiping test were also conducted using the same method as in Japanese Patent No. 6723489. The ambient temperature at the wiping test location and the static friction coefficient measurement location were 25±3°C, 50±10%, and atmospheric pressure.
[0090] In this wiping test, a long fiber nonwoven fabric (50 mm in length in the wiping direction) made of cotton linter containing rubbing alcohol was applied to the surface of the coating 24 in a 2×10 -3 MPa~4×10 -3The surface of the coating 24 was wiped 20,000 times (10,000 reciprocating strokes) at a speed of 80-120 times / min, with a length of 150 mm in the wiping direction, so that a shear stress of 100 MPa was applied. As a result, the difference (absolute value) before and after the test in the static friction coefficient of the coating 24 of samples C11 and C12 was 0.019 and 0.047, respectively, both of which were below 0.1. Table 4 below shows the measured values of the static friction coefficient of the coating 24 of samples C11 and C12.
[0091] [Table 4]
[0092] On the other hand, when the surface conditions of samples C11 and C12 were observed by SEM before and after the wiping test, differences were found between the two.
[0093] Figures 16(a) and (b) are observation images (1000x) of the surfaces of samples C11 and C12, respectively, before the wiping test. Figures 17(a) and (b) are observation images of the surfaces of samples C11 and C12, respectively, after the wiping test. The spherical particles and the white powder particles around them observed in the observation images in Figures 16(a), (b) and Figures 17(a), (b) are fine particles 112 and TiO2 fine particles 113, respectively.
[0094] As shown in Figures 16(a) and 16(b), more voids were observed in the coating 24 of sample C10 than in the coating 24 of sample C11. Furthermore, as shown in Figures 17(a) and 17(b), more particles 112 fell off from the coating 24 of sample C12 than from the coating 24 of sample C11. One of the main reasons for these results is thought to be that the concentration of TiO particles 113 in the coating 24 (second layer 11) of sample C12 was too high. The presence of more TiO particles 113 around the particles 112 reduced the contact area between the silicone rubber base material 111 and the particles 112, resulting in reduced adhesion. The results of the wiping test and SEM observation confirmed that the upper limit of the Ti concentration in the coating 24 was 4.4% by mass.
[0095] The preferred ranges of the Ti concentration in the first layer 10 containing TiO2 particles 102 and the Ti concentration in the second layer 11 containing TiO2 particles 113, which were explained using Figure 2 in the first embodiment, were derived based on the test results of this example.
[0096] (Summary of the embodiment) Next, the technical ideas grasped from the above-described embodiments will be described by using the reference numerals and the like in the embodiments. However, the reference numerals and the like in the following description do not limit the components in the claims to the members and the like specifically shown in the embodiments.
[0097] [1] Silicone rubber is used as the base material (101), and the first TiO 2 A first layer (10) containing fine particles (102) and a second TiO 2 and a second layer (11) containing fine particles (113), wherein the Ti concentration of the first layer (10) is 0.35 mass% or more and 3.0 mass% or less, the Ti concentration of the second layer (11) is 1.0 mass% or more and 4.4 mass% or less, and the Ti concentration of the second layer (11) is higher than the Ti concentration of the first layer (10); 1404J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light of 1404 J / cm is 250% or more, and 2 A laminated structure (1) in which, when subjected to a bending test equivalent to 45 to 50% tensile strength after irradiation with UV-C ultraviolet light, cracks are observed in three or fewer areas of 1.5 mm x 4.5 mm at ten locations on the surface at a magnification of 50 times using an optical microscope.
[0098] [2] Silicone rubber is used as the base material (101), and the first TiO 2 A first layer (10) containing fine particles (102) and a second TiO 2 and a second layer (11) containing fine particles (113), wherein the Ti concentration of the first layer (10) is 0.35 mass% or more and 3.0 mass% or less, the Ti concentration of the second layer (11) is 1.0 mass% or more and 4.4 mass% or less, and the Ti concentration of the second layer (11) is higher than the Ti concentration of the first layer (10); 2808J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light of 2808 J / cm is 150% or more, and 2 A laminated structure (1) in which, when subjected to a bending test equivalent to 45 to 50% tensile strength after irradiation with UV-C ultraviolet light, cracks are observed in three or fewer areas of 1.5 mm x 4.5 mm at ten locations on the surface at a magnification of 50 times using an optical microscope.
[0101] [5] The above [, wherein the second layer (11) contains at least one of silicone resin fine particles and silica fine particles. 1 ] or [ 2] The laminated structure (1) according to the present invention.
[0102] [6]The above[ 1 ]~[ 3 A cable (20) comprising an insulator (23, 24) made of the laminated structure (1) according to any one of the preceding claims.
[0103] [7]The above[ 1 ]~[ 3 10. A tube (40a, 40b, 40c) comprising an insulator (41, 42, 43) made of the laminated structure (1) according to any one of claims 1 to 9.
[0104] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above embodiments and examples, and various modifications are possible within the scope of the gist of the invention. Furthermore, the above-described embodiments and examples do not limit the invention according to the claims. Furthermore, it should be noted that not all of the combinations of features described in the embodiments and examples are necessarily essential to the means for solving the problems of the invention. [Explanation of symbols]
[0105] 1. Laminated structure 10 First Layer 101 Base material 102 TiO2 fine particles 11 Second Layer 111 Base material 112 Fine particles 113 TiO2 fine particles 2 Ultrasound probe cables 20 Cable 23 Sheath 24 Coating 40a, 40b, 40c Medical tubing 41 Tube body 42 Outer coating 43 Inner capsule
Claims
1. A first layer having a silicone rubber base material and including first TiO 2 fine particles; a second layer made of silicone rubber and containing second TiO 2 fine particles, laminated on the first layer; Equipped with The Ti concentration of the first layer is 0.35 mass % or more and 3.0 mass % or less, The Ti concentration of the second layer is 1.0 mass % or more and 4.4 mass % or less, the second layer has a higher Ti concentration than the first layer; 1404 J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light is 250% or more, The 1404 J / cm 2 When a bending test equivalent to 45 to 50% tensile strength is performed after irradiation with UV-C ultraviolet light, when 10 areas of 1.5 mm x 4.5 mm on the surface are observed at a magnification of 50 times using an optical microscope, cracks are observed in 3 or less areas. Laminated structure.
2. A first layer having a silicone rubber base material and including first TiO 2 fine particles; a second layer made of silicone rubber and containing second TiO 2 fine particles, laminated on the first layer; Equipped with The Ti concentration of the first layer is 0.35 mass % or more and 3.0 mass % or less, The Ti concentration of the second layer is 1.0 mass % or more and 4.4 mass % or less, the second layer has a higher Ti concentration than the first layer; 2808 J / cm 2 The elongation at break measured by a tensile test after irradiation with UV-C light is 150% or more, The 2808 J / cm 2 When a bending test equivalent to 45 to 50% tensile strength is performed after irradiation with UV-C ultraviolet light, when 10 areas of 1.5 mm x 4.5 mm on the surface are observed at a magnification of 50 times using an optical microscope, cracks are observed in 3 or less areas. Laminated structure.
3. the second layer comprises at least one of silicone resin particulates and silica particulates; The laminated structure according to claim 1 or 2.
4. An insulating material comprising the laminated structure according to any one of claims 1 to 3. cable.
5. An insulating material comprising the laminated structure according to any one of claims 1 to 3. tube.
Citation Information
Patent Citations
Cables and medical hollow tubes
JP6723489B1
JPP6876262B